2012
DOI: 10.1002/etc.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations of a resident freshwater forage fish at Adak Island, Aleutian Archipelago, Alaska

Abstract: The Aleutian Archipelago is an isolated arc of over 300 volcanic islands stretching 1,600 km across the interface of the Bering Sea and North Pacific Ocean. Although remote, some Aleutian Islands were heavily impacted by military activities from World War II until recently and were exposed to anthropogenic contaminants, including mercury (Hg). Mercury is also delivered to these islands via global atmospheric transport, prevailing ocean currents, and biotransport by migratory species. Mercury contamination of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Pollution is a significant threat to island freshwater ecosystems. A number of studies identified in this review reported high concentrations of bioaccumulating pollutants, such as mercury, in freshwater ecosystems (Jaffal et al 2011;Zananski et al 2011), including in isolated islands in the Arctic and Antarctic regions (Riget et al 2004;St Louis et al 2005;Kenney et al 2012). Agricultural activities are also a source of nutrients (Duwig et al 1998;Caruso 2002;Corbet et al 2002) and agrochemicals (Magbanua et al 2010;Tashiro et al 2013), which can reduce the quality of freshwater resources.…”
Section: Freshwatermentioning
confidence: 88%
“…Pollution is a significant threat to island freshwater ecosystems. A number of studies identified in this review reported high concentrations of bioaccumulating pollutants, such as mercury, in freshwater ecosystems (Jaffal et al 2011;Zananski et al 2011), including in isolated islands in the Arctic and Antarctic regions (Riget et al 2004;St Louis et al 2005;Kenney et al 2012). Agricultural activities are also a source of nutrients (Duwig et al 1998;Caruso 2002;Corbet et al 2002) and agrochemicals (Magbanua et al 2010;Tashiro et al 2013), which can reduce the quality of freshwater resources.…”
Section: Freshwatermentioning
confidence: 88%
“…Fish and Wildlife Service in their efforts to manage for contaminant exposure of wildlife within the Alaska Maritime National Wildlife Refuge. Determination of management concerns can be facilitated by the monitoring of important fish prey species of higher trophic level wildlife (Kenney et al., 2012, 2014). PCB data from Unalaska also contribute to the understanding of ecotoxicology in a poorly studied region of the Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hg concentrations in stickleback from Agattu Island were higher than would be expected for an area without a known point source of Hg pollution, other studies have documented comparatively high concentrations of contaminants in marine organisms from the western Aleutians [8] [10] , [13] , [30] . Recent work at Adak Island, located in the central Aleutians, also revealed similarly high mean Hg concentrations in resident freshwater stickleback populations (range = 0.31–0.54 µg/g dw) [22] . The Aleutian Low, a semi-permanent low-pressure system characterized by many strong cyclones, dominates weather patterns of the North Pacific and Bering Sea.…”
Section: Discussionmentioning
confidence: 83%
“…Recent work at Adak Island, located in the central Aleutians, also revealed similarly high mean Hg concentrations in resident freshwater stickleback populations (range  = 0.31–0.54 µg/g dw) [22]. The Aleutian Low, a semi-permanent low-pressure system characterized by many strong cyclones, dominates weather patterns of the North Pacific and Bering Sea.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation